Phytochemical profile of Trigonella caerulea (Blue Fenugreek) herb and quantification of aroma-determining constituents - Arpine Ayvazyan and Thomas Stegemann and Mayra Galarza Pérez and Manuel Pramsohler and Serhat Sezai Çiçek (Plants, 2023)
The herb of Trigonella caerulea (Fabaceae), commonly known as blue fenugreek, is used for the production of traditional cheese and bread varieties in the Alpine region. Despite its frequent consumption, only one study so far has focused on the constituent pattern of blue fenugreek, revealing qualitative information on some flavor-determining constituents. However, with regard to the volatile constituents present in the herb, the applied methods were insufficient and did not take relevant terpenoids into account. In the present study, we analyzed the phytochemical composition of T. caerulea herb applying a set of analytical methods, such as headspace-GC, GC-MS, LC-MS, and NMR spectroscopy. We thus determined the most dominant primary and specialized metabolites and assessed the fatty acid profile as well as the amounts of taste-relevant α-keto acids. In addition, eleven volatiles were quantified, of which tiglic aldehyde, phenylacetaldehyde, methyl benzoate, n-hexanal, and trans-menthone were identified as most significantly contributing to the aroma of blue fenugreek. Moreover, pinitol was found accumulated in the herb, whereas preparative works led to the isolation of six flavonol glycosides. Hence, our study shows a detailed analysis of the phytochemical profile of blue fenugreek and provides an explanation for its characteristic aroma and its health-beneficial effects.
Keywords: camphor; cymene; flavonoids; glyoxylic acid; kaempferol; ketoglutaric acid; linoleic acid; linolenic acid; pyruvic acid; quercetin